"One Degree of Separation": A Mixed-Methods Evaluation of Canadian Mental Health Care User and Provider Experiences With Remote Care During COVID-19. (September 2022) - Ceniti, Amanda K.; Abdelmoemin, Wegdan R.; Ho, Keith; Kang, Yudi; Placenza, Franca; Laframboise, Rachel; Bhat, Venkat; Foster, Jane A.; Frey, Benicio N.; Lam, Raymond W.; Milev, Roumen; Rotzinger, Susan; et al.
Objectives: The COVID-19 pandemic has contributed to a shift from in-person to remote mental health care. While remote care methods have long existed, their widespread use is unprecedented. There is little research about mental health care user and provider experiences with this transition, and no published studies to date have compared satisfaction between these groups. Methods: Canadian mental health care users ( n = 332) and providers ( n = 107) completed an online self-report survey from October 2020 to February 2021 hosted by the Canadian Biomarker Integration Network in Depression. Using a mixed-methods approach, participants were asked about their use of remote care, including satisfaction, barriers to use, helpful and unhelpful factors, and suggestions for improvement. Results: Overall, 59% to 63% of health care users and 59% of health care providers were satisfied with remote care. Users reported the greatest satisfaction with the convenience of remote care, while providers were most satisfied with the speed of provision of care; all groups were least satisfied with therapeutic rapport. Health care providers were less satisfied with the user-friendliness of remote care ( P < 0.001) than users, while health care users were less satisfied than providers with continuity of care ( P < 0.001). The use of a video-based platform was associated with remote care satisfaction among health care users ( P < 0.02), and qualitative responses support the importance of visual cues in maintaining therapeutic rapport remotely. The majority of users (55%) and providers (87%) reported a likelihood of using remote care after the pandemic. Conclusions: Remote mental health care is generally accepted by both users and providers, and the majority would consider using remote care following the pandemic. Suggestions for improvement include greater use of video, increased attention to body language and eye contact, consistency with in-person care, as well as increased provider training and administrative support.